THE DISCOVERY OF BALMEISPORITES AND ITS SIGNIFICANCE OF TAIPINGLINCHANG FORMATION IN JIAYIN BASIN, HEILONGJIANG - Wan C.; Shan X.; Ren Y.; Liu B.; Qiao X.; Yang J. (My University, 2004)
Indications of oil and gas have been found in the mudstone of Taipinglinchang formation in Sunwu-Jiayin basin which is the second important basin for exploration outside Daqing oil field in 2001. Abundant Balmeisporites including Balmeisporites cf. kondinskayae Srivastava et Binda, Balmeisporites jiayinensis sp. nov., Balmeisporites taipinglinchangensis sp. nov., Balmeisporites?sp. 1 and Balmeisporites?sp. 2, have been found for first time in the mudstone lower Taipinglinchang Formation. The discovery is abundant of fossils in the section that Taipinglinchang Formation was established, and provides important basis for correlation of lithologic stratum units and outcrop sections. The Balmeisporites being not type with the equator processes show typical characteristics of Later Cretaceous. The fossils of Spore-pollen, Ostracoda and conchostracans being Later Cretaceous Santoian-Campanian in the formation can be correlated to that of Songliao basin. Palaeoclimate indicated by the Balmeis porites was moist subtropics, and palaeoenvironment of stratum including Balmeis porites was delta front or prodelta.